PERENCANAAN PENCEGAHAN TANAH LONGSOR DENGAN METODE DINDING PENAHAN TANAH - Agussalim Patola DM; Raden Wirawan (Fakultas Teknik Universitas Muhammadiyah Parepare, 2023)
A landslide is the displacement of slope-forming material in the form of rock, material, soil, or mixed material moving down or out of the slope. The causes of landslides vary from one location to another. The purpose of this study is to determine the characteristics of soil mechanics in determining the carrying capacity of the soil in planning landslide handling with the method of building a retaining wall. The methods used in this study started from visual identification, field testing and laboratory testing. The results of this study obtained that the condition of the soil at the coordinate point S.02041'47.25